Pengaruh Konsumsi Listrik, Pertumbuhan Ekonomi, Industrialisasi, dan Keterbukaan Perdagangan terhadap Emisi CO2 di Indonesia tahun 1983-2019 - Atik Rahmawati; Mulyo Hendarto Robertus (Universitas Diponegoro, 2023)
Many developing countries including Indonesia are still largely dependent on fossil fuel power plants, even though the negative impact results in an increase in carbon emissions. In this study, the driving factors for emissions are seen from electricity consumption, GDP, industry value added and the ratio total exports of GDP. This study aims to look at the relationship between electricity consumption, economic growth, industrialization, and trade openness on CO2 carbon emissions in Indonesia in 1983-2019. This study uses secondary data in the form of time series data. Analysis in this study uses the Error Correction Model-Engle Granger (ECM-EG) method for short-term estimation and the Cointegration Test for long-term estimation. The results showed that in the long run electricity consumption and industrialization had a significant positive effect on CO2 carbon emissions. In the short term, only economic growth has a positive effect on carbon emissions.